Leiomyoma of the breast parenchyma: a case report and review of the literature - Rodrigo Gregório Brandão; Simone Elias; Afonso Celso Pinto Nazário; Maria do Carmo Guedes Alcoforado Assunção; Camilla Cirone Esposito Papa; Gil Facina (São Paulo Medical Journal, 2017)
ABSTRACT INTRODUCTION: Benign tumors are often seen in breast screening examinations. However, the differential diagnosis is not always simple because of radiological similarity between the different benign lesions. CASE REPORT: We present a rare case report of leiomyoma of the breast parenchyma in a 68-year-old asymptomatic patient. The mammographic and ultrasonographic findings were similar to those observed in benign lesions. CONCLUSION: The histopathological diagnosis requires careful differentiation from lesions that have smooth muscle proliferation, especially leiomyosarcoma. The most commonly performed treatment is resection of the lesion with free margins. Although breast leiomyoma is rare, it should be considered among the differential diagnoses for breast nodules of benign appearance. Resection with safety margins proved to be the only treatment needed.